Exporting New Zealand education services : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Hanna, Nita (Massey University, 1993)
The entry of New Zealand state education into the export market provided an unique opportunity for the researcher to combine interests in education, exporting, marketing and finance. The challenge was to investigate an entirely new export industry which was growing at a very rapid rate. In the absence of other studies relating to the New Zealand situation, information was obtained from relevant documents, interviews with people associated with aspects of the industry and questionnaires to students in selected institutions and to a spokesperson for overseas students within each of the institutions. The intended benefits and possible pitfalls perceived by people associated with forming the legislation were identified. In addition to the expected financial gains a number of non-financial benefits based on past experience with government assisted students were revealed. They related to trade and internationalisation. Some were of a very long-term nature. Anticipated problems were largely associated with traditional attitudes about the role of state education in New Zealand. The study revealed: There were wide differences of opinion on the role of legislation and on the policies which should be adopted. Students, unlike respondents from New Zealand institutions, did not consider the high standard of New Zealand education qualifications their main reason for choosing New Zealand as an educational destination. Although students tended to compare aspects of New Zealand with those of their home country, there was overall agreement about liking the cultural experience, the way of life, the people, and the New Zealand countryside. Students adapted to most differences in teaching institutions between New Zealand and their home country within one year, except mastery of the English language. Spokespeople for institution did not indicate language was such a persistent problem. Aspects of New Zealand students would most like to change included costs (especially rising costs) and the attitudes of some New Zealanders to foreigners. Respondents from institutions believed there was a very large market for New Zealand education, but the rate of growth was dependent on the acceptability of numbers of overseas students by New Zealanders. There was very little difference between fee-paying and government funded students' responses. Lack of funding has restricted some generic activities including a co-ordinated approach to catering for student's needs once they are in New Zealand.
Keywords: New Zealand; Education (Higher); Education; Marketing; Students, Foreign; Education -- Economic aspects